Interpreting China's grand strategy : past, present, and future - Swaine, Michael D.; Tellis, Ashley J. (Project Air Force report., 2000)
China's continuing rapid economic growth and expanding involvement in global affairs pose major implications for the power structure of the international system. To more accurately and fully assess the significance of China's emergence for the United States and the global community, it is necessary to gain a more complete understanding of Chinese security thought and behavior. This study addresses such questions as: What are China's most fundamental national security objectives? How has the Chinese state employed force and diplomacy in the pursuit of these objectives over the centuries? What s.